PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KNOWLEDGE SHARING SISWA DI SMK PUTRA JAYA SCHOOL - Sautpin Saragih (Computer Based Information System Journal, 2015)
Implementation of information technology is hardware-based computer (hardware), software (software) and user (Users). Presently Information Technology has been fundamental. (Hardware) is the medium used to process information. Software (software) that systems and applications used to process inputs (input) to be informed. Users of the system are human (man) that psychology has a behavior (behavior) certain inherent, so that aspect in the context of human habits as a user (brain ware) of information technology is important as a determinant factor in every person running information technology. Sharing knowledge (knowledge sharing) is a very important part in knowledge management where this activity will make the knowledge or experience of students can spread wide and share to friends or the entire element is o the students environment . This study aims to determine the effect of the use of information technology to employee performance SMK Putra Jaya School.